Supporting New Physicians and New Parents: A Call to Create A Standard Parental Leave Policy for Residents. (9th July 2019) - Ortiz Worthington, Rebeca; Feld, Lauren D.; Volerman, Anna
Abstract : Parents taking leave after the birth of a child is associated with significant benefits for infants, mothers, and fathers. Although nearly 40% of residents have or plan to have children during residency, there is no standard parental leave policy for these trainees. In this Perspective, the authors discuss the benefits of parental leave, synthesize findings about maternity bias and other negative effects of the current variable approaches to parental leave during residency, and explore underlying causes of the lack of a standard parental leave policy for residents. They also call on the Accreditation Council for Graduate Medical Education and the American Board of Medical Specialties to work together to address this issue, recommending a standard parental leave policy that ensures a minimum of eight weeks of paid leave for all residents without requiring them to extend training or becoming ineligible to sit for board certification exams. Creating evidence-based and family-friendly guidelines for parental leave is important to the progress of academic medicine in the modern era, as it supports parental and child health, promotes resident wellness, and reduces gender disparities in medicine to the benefit of all.